Empowerment of Partner Schools Through the Development of the Mini Bank Application (m-MiniBank) at SMKN 7 Bandar Lampung - Mugi Praseptiawan; ilham Firman Ashari; Samsu Bahri; Meida Cahyo Untoro; Arre Pangestu; Aidil Afriasnyah; Muhammad Habib Algifari (Peneliti Teknologi Teknik Indonesia, 2023)
SMKN 7 Bandar Lampung is an educational unit that manages a Mini Bank which is used for teaching factory practices in financial accounting practices, besides that it is also a school designated by the regional government of Lampung province which heads the Lampung regional public service agency (BLUD). The problems faced in the management of mini-banks are that the business processes are not running optimally, the transaction process is running manually, besides that the manager's capacity knowledge is also inadequate in managing it. The purpose of this community service activity is to develop the capacity and capabilities of partner schools through the development of the Mini Bank application. The empowerment method used is starting from identifying needs and problems, application design, implementation, testing, and finally evaluation. The result of this dedication is a mini bank application with testing carried out involving 10 respondents, the results of the UEQ (User Experience Questionnaire) test show the value of the efficiency aspect is 2.15, the accuracy aspect is 2.14, the clarity aspect is 2.44, the stimulation aspect that is 2.15 and the attractiveness aspect is 2.26 so that the scores on all aspects get an excellent score.